AB1161-HPR The Subjective Vitality Scale is an Indicator of Physical and Psychological Health Amongst Rheumatoid Arthritis Patients. (10th June 2014) - Rouse, P.; Veldhuijzen Van Zanten, J.; Metsios, G.; Yu, C.-A.; Ntoumanis, N.; Kitas, G.; Duda, J.L.
Abstract : Background: Rheumatoid arthritis (RA) is the most prevalent chronic inflammatory arthritis characterized by periods of remission and flares in disease activity unique to each individual. Consequently, patients with RA experience fluctuations in both physical and psychological health and well-being (1). Subjective vitality is an indicator of positive health/optimal functioning and has been conceptualised as a sense of being alive and full of energy. Therefore, if the Subjective Vitality Scale (2) demonstrates convergent validity with indicators of physical and psychological health in RA patients, it could provide a brief and clinically relevant assessment tool. Objectives: To investigate the associations between subjective vitality and indicators of physical health (i.e. physical function and cardio-respiratory fitness), and psychological health (i.e. quality of life, fatigue, depression and anxiety) amongst RA patients. Methods: Patients with RA ( N =106, age 54.5±12.3 years, 68% women) completed a questionnaire pack and an exercise tolerance test to assess cardio-respiratory fitness (VO2max).The Subjective Vitality Scale contains five items (e.g. "I feel alive and full of vitality"). Participants responded to how much vitality, over the last two weeks, they felt, using a scale anchored by 1 ( not at all true ) and 7 ( very true ). Participants were also asked to complete the following measures: Multidimensional Assessment of Fatigue to measure physical function, (3) Hospital Anxiety and Depression Scales, (4) Health Assessment Questionnaire to measure physical function (5) and the EuroQol (6). A blood sample was provided to measure C-reactive protein, an indicator of disease activity. Results: Partial correlations were conducted controlling for age, gender and disease activity. Results revealed significant ( p <0.05) positive relationships between subjective vitality and two indicators of physical health (function r =0.55 and fitness r =0.22). Significant relationships, in the expected direction, were also observed between subjective vitality and indicators of psychological health (Quality of Life r =0.60, Fatigue r = -0.66, Depression r = -0.73 and anxiety r = -0.57). Conclusions: The Subjective Vitality Scale is a brief self-reported questionnaire that associates with improvements in both physical and psychological health amongst patients with RA. These significant associations support the convergent validity of the instrument. Healthcare professional could use the Subjective Vitality Scale to identify RA patients experiencing compromised physical health and well-being as well as provide an additional outcome measure to assess the effectiveness of treatment programmes. References: Covic T, Cumming S, Pallant J, Manolios N, Emery P, Conaghan P, et al. Depression and anxiety in patients with rheumatoid arthritis: prevalence rates based on a comparison of the Depression, Anxiety and Stress Scale (DASS) and the hospital, Anxiety and Depression Scale (HADS). BMC Psychiatry 2012;12(1):6. Ryan RM, Frederick C. On energy, personality, and health: Subjective vitality as a dynamic reflection of well-being. Journal of Personality 1997;65(3):529-65. Acknowledgements: Medical Research Council and NPRI Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5037